Application of artificial intelligence in rabbit husbandry: from reproductive monitoring to precision farming - Abdel-Wareth, Ahmed A. A.; Ahmed, Ahmed A.; Salahuddin, Md; Lohakare, Jayant (Frontiers in Veterinary Science, 2025)
Artificial Intelligence (AI) is revolutionizing animal husbandry by automating and optimizing management processes, with significant potential in rabbit farming. Due to rabbits’ high reproductive rates and diverse uses, AI can greatly improve reproductive management, health monitoring, and behavior analysis, as well as reproductive monitoring, health assessment, and precision farming. AI technologies, such as machine learning (ML), computer vision, and sensor integration, enable more efficient pregnancy detection, parturition prediction, delivery monitoring, and health surveillance. These systems innovations reduce reliance on manual labor, minimize monitoring time, and enhance animal welfare. AI-powered systems can detect pregnancy and predict parturition by analyzing physiological data, while wearable sensors and machine learning models monitor real-time health data information to identify early signs of illness. Additionally, AI tools track rabbits’ behavior, activity levels, and social interactions, ensuring optimal living conditions and reducing stress or injury. However, challenges remain, including data collection, ethical concerns, and adapting systems to diverse farming environments. Despite these obstacles, AI offers substantial benefits, including precision management, increased productivity, and improved animal wellbeing. As AI technologies evolve, further advancements in accessibility, affordability, and integration into existing farm management systems are necessary. The integration of AI in rabbit husbandry can foster sustainable and humane practices, providing data-driven insights for better decision-making. This review highlights how AI innovations will revolutionize rabbit farming and lay the groundwork for broader applications in livestock management, contributing to the global expansion of precision farming.